(untitled) (Eurasian Medical Research Periodical, 2026)
The nocebo effect is a psychoneurobiological phenomenon in which negative expectations, beliefs, and verbal suggestions lead to measurable physiological and psychological changes in the human body. It is considered the inverse counterpart of the placebo effect, where instead of improvement through positive expectations, harm or worsening of symptoms occurs due to negative anticipation. The mechanism of the nocebo effect is closely related to cognitive appraisal and the brain’s stress-response systems. When a person is exposed to negative information—such as warnings about side effects, pessimistic predictions, or harmful labels—the brain activates stress-related pathways, including the hypothalamic-pituitary-adrenal (HPA) axis. This activation leads to increased cortisol release, heightened anxiety, and changes in pain perception